Computational Tools for Serial Block Electron Microscopy Reveal Plasmodesmata Distributions and Wall Environments. Issue 1 (23rd July 2020) - Paterlini, Andrea; Belevich, Ilya; Jokitalo, Eija; Helariutta, Yrjö
Abstract: Computational tools for serial block electron microscopy data sets can extract information on the cell wall environment and spatial distribution of plasmodesmata over an entire cellular interface. Abstract: Plasmodesmata are small channels that connect plant cells. While recent technological advances have facilitated analysis of the ultrastructure of these channels, there are limitations to efficiently addressing their presence over an entire cellular interface. Here, we highlight the value of serial block electron microscopy for this purpose. We developed a computational pipeline to study plasmodesmata distributions and detect the presence/absence of plasmodesmata clusters, or pit fields, at the phloem unloading interfaces of Arabidopsis ( Arabidopsis thaliana ) roots. Pit fields were visualized and quantified. As the wall environment of plasmodesmata is highly specialized, we also designed a tool to extract the thickness of the extracellular matrix at and outside of plasmodesmata positions. We detected and quantified clear wall thinning around plasmodesmata with differences between genotypes, including the recently published plm-2 sphingolipid mutant. Our tools open avenues for quantitative approaches in the analysis of symplastic trafficking.